Correlations of Myeloperoxidase (MPO), Adenosine deaminase (ADA), C–C motif chemokine 22 (CCL22), Tumour necrosis factor alpha (TNFα) and Interleukin-6 (IL-6) mRNA expression in the nasopharyngeal specimens with the diagnosis and severity of SARS-CoV-2 infections - Kelvin Hei-Yeung Chiu; Cyril Chik-Yan Yip; Rosana Wing-Shan Poon; Kit-Hang Leung; Xin Li; Ivan Fan-Ngai Hung; Kelvin Kai-Wang To; Vincent Chi-Chung Cheng; Kwok-Yung Yuen (Emerging Microbes and Infections)
Cytokine dynamics in patients with coronavirus disease 2019 (COVID-19) have been studied in blood but seldomly in respiratory specimens. We studied different cell markers and cytokines in fresh nasopharyngeal swab specimens for the diagnosis and for stratifying the severity of COVID-19. This was a retrospective case-control study comparing Myeloperoxidase (MPO), Adenosine deaminase (ADA), C–C motif chemokine ligand 22 (CCL22), Tumour necrosis factor alpha (TNFα) and Interleukin-6 (IL-6) mRNA expression in 490 (327 patients and 163 control) nasopharyngeal specimens from 317 (154 COVID-19 and 163 control) hospitalized patients. Of the 154 COVID-19 cases, 46 died. Both total and normalized MPO, ADA, CCL22, TNFα, and IL-6 mRNA expression levels were significantly higher in the nasopharyngeal specimens of infected patients when compared with controls, with ADA showing better performance (OR 5.703, 95% CI 3.424–9.500, p < 0.001). Receiver operating characteristics (ROC) curve showed that the cut-off value of normalized ADA mRNA level at 2.37 × 10–3 had a sensitivity of 81.8% and specificity of 83.4%. While patients with severe COVID-19 had more respiratory symptoms, and elevated lactate dehydrogenase, multivariate analysis showed that severe COVID-19 patients had lower CCL22 mRNA (OR 0.211, 95% CI 0.060–0.746, p = 0.016) in nasopharyngeal specimens, while lymphocyte count, C-reactive protein, and viral load in nasopharyngeal specimens did not correlate with disease severity. In summary, ADA appears to be a better biomarker to differentiate between infected and uninfected patients, while CCL22 has the potential in stratifying the severity of COVID-19.